Effect of Therapy by Using Advocate Spot-On Combination (Imidacloprid 10% and Moxidectin 2.5%) on Subcutaneous Dirofilariosis in Dogs - Radmila Dobešová Paran; Vlasta Svobodová (Veterinary Medicine International)
Dirofilaria (Nochtiella) repens is a filarioid parasite that causes subcutaneous dirofilariosis in dogs. Adults, while localized in subcutaneous tissues, lay embryos (microfilariae (mf)) into the blood stream of dogs, which constitute a reservoir for infection of other definitive or accidental hosts as humans. This study was carried out to assess the efficacy of spot-on combination of imidacloprid and moxidectin on microfilariaemia in naturally infected dogs. A group of 11 dogs was monthly examined for the presence of microfilariae in peripheral blood by modified Knott's test method. Treatment was administered monthly for 4 months. All dogs (i.e., 100%) became negative for microfilariaemia throughout the study. These results confirm the effect of the combination of imidacloprid and moxidectin on D. (Nochtiella) repens.